Innovative design on technology of urban Darrieus VAWT: field tests - Melicio, Rui (2015)
This paper is about an innovative design for an urban Darrieus Vertical Axis Wind Turbine (VAWT), having the ability of having self-start at low wind velocities, but without the need for extra components or external electricity feed-in. A new mathematical model to assess complex shaped Darrieus VAWT prototype is presented in this paper and offers a new approach to the Double Multiple Streamtube model. Field tests to assess the behavior of the prototype and main conclusions are presented.